The Roles of Privacy and Trust in Children's Evaluations and Explanations of Digital Tracking. Issue 5 (12th June 2021) - Gelman, Susan A.; Cuneo, Nicole; Kulkarni, Sanika; Snay, Sarah; Roberts, Steven O.
Abstract : A "digital revolution" has introduced new privacy violations concerning access to information stored on electronic devices. The present two studies assessed how U.S. children ages 5–17 and adults ( N = 416; 55% female; 67% white) evaluated those accessing digital information belonging to someone else, either location data (Study 1) or digital photos (Study 2). The trustworthiness of the tracker (Studies 1 and 2) and the privacy of the information (Study 2) were manipulated. At all ages, evaluations were more negative when the tracker was less trustworthy, and when information was private. However, younger children were substantially more positive overall about digital tracking than older participants. These results, yielding primarily medium‐to‐large effect sizes, suggest that with age, children increasingly appreciate digital privacy considerations.